Screening for Cancer in Patients with Acute Venous Thromboembolic Disease - Blondon, Marc (Hämostaseologie, 2021)
Active cancer causes approximately 25% of all acute events of venous thromboembolism (VTE). While most of the cancer diagnoses are known or clinically apparent at the time of VTE, care providers and patients may be worried about the 3 to 8% risk of occult cancer occurring in the year after VTE. Several studies have compared limited to extensive cancer screening after acute VTE, especially with the addition of abdominal computed tomography (CT) or whole-body PET-CT, with the hope to shorten the time to cancer diagnosis and lead to less advanced cancer stages. These studies have not shown improved clinical outcomes with an extensive screening, and have led to current recommendations of limited screening for cancer in patients with acute VTE, including unprovoked cases. Several risk assessment models have been developed to identify patients at greatest risk of occult cancer, however, with low discriminative performances and no current clinical usefulness. Some clinical situations may empirically deserve a more thorough cancer screening, such as unprovoked upper extremity deep vein thrombosis (DVT), bilateral leg DVT, descending leg DVT, or recurrent VTE during anticoagulation.
Keywords: venous thrombosis; cancer; pulmonary embolism; diagnosis